Go reconfigure [programmable logic in handheld devices]. - Tredennick, N. (IEEE spectrum)
The article discusses why only programmable handheld devices can do the job of any 10 different gizmos. The development of a chameleon-like handheld device is also described. The programmable logic device (PLD), a semiconductor containing a personalization memory and logic elements, can make it possible to have a pocket-electronics device consolidated with a number of features including adaptability to any network, capability to fit new standards, and having an upgradeable security system for the latest virus. Conventional PLDs are big, slow, power hungry, and expensive, but, like the microprocessors, PLDs can evolve in time into higher-level logic primitives that make them suitable for untethered applications.